The Patterns of Primary Cotrimoxazole Prophylaxis in Adult HIVPatients in HIV Integrated Clinic Cipto Mangunkusumo HospitalJakarta in 2004-2013 - Mastini, Ken Ayu; Djoerban, Zubair; Yunihastuti, Evy (Jurnal Penyakit Dalam Indonesia, 2017)
Introduction. Low rate use of cotrimoxazole which is a standard of primary prevention against toxoplasmosis infection and Pneumocystis jirovecii pneumonia (PCP) in patients with CD4 <200 cell>/mm3 was found. This study aims to describe prescription pattern of cotrimoxazole primary prophylaxis in adult HIV patients in RSCM. Methods. A cohort retrospective study was conducted in HIV Integrated Clinic Cipto Mangunkusumo Hospital patients from 2004 to 2013. Individuals were eligible for this study if they were ≥18 years old and had indication of primary cotrimoxazole prophylaxis. Variable analyzed in this study were initiation, discontinuation, dosage, duration, duration percentage, and adverse events of primary cotrimoxazole prophylaxis. Results. A total of 3.818 patients had indication of primary cotrimoxazole prophylaxis. Initiation of primary cotrimoxazole prophylaxis was performed in 83% patients who met indication. Total od 99,8% patients used appropriate dose of cotrimoxazole. Frequent adverse events were increasing hepatic transaminase (38,1%), leucopenia (16,9%), anemia (16,5%), nausea (15,4%), vomiting (7,8%), thrombocytopenia (7,4%), and hypersensitivity (5,3%). Adverse event causing discontinuation were hypersensitivity (100%), anemia (2,4%), increasing hepatic transaminase (2,1%), vomiting (0,8%), and leucopenia (0,6%). Inappropriate discontinuation of cotrimoxazole was 61,6% with median duration percentage was 87,5% (IQR 39) and median of duration was 20 months (IQR 20). Duration in patients with CD4 ≤100 cell/mm3 and >100 cell/mm3 was 21 months (IQR 22) and 12,5 months (IQR 14,75) p <0,001. Conclusion. Although initiation of primary cotrimoxazole prophylaxis was done in 83% adult HIV patients with appropriate dosage, it was found that 61,6% discontinuation was inappropriate according with guideline.